Polycomb group proteins Ring1A/B are functionally linked to the core transcriptional regulatory circuitry to maintain ES cell identity. - Endoh, M; Endo, T; Endoh, T; Fujimura, Y; Ohara, O; Toyoda, T; Otte, A; Okano, M; Brockdorff, N; Vidal, M; Koseki, H (2008)
The Polycomb group (PcG) proteins mediate heritable silencing of developmental regulators in metazoans, participating in one of two distinct multimeric protein complexes, the Polycomb repressive complexes 1 (PRC1) and 2 (PRC2). Although PRC2 has been shown to share target genes with the core transcription network, including Oct3/4, to maintain embryonic stem (ES) cells, it is still unclear whether PcG proteins and the core transcription network are functionally linked. Here, we identify an essential role for the core PRC1 components Ring1A/B in repressing developmental regulators in mouse ES cells and, thereby, in maintaining ES cell identity. A significant proportion of the PRC1 target genes are also repressed by Oct3/4. We demonstrate that engagement of PRC1 at target genes is Oct3/4-dependent, whereas engagement of Oct3/4 is PRC1-independent. Moreover, upon differentiation induced by Gata6 expression, most of the Ring1A/B target genes are derepressed and the binding of Ring1A/B to their target loci is also decreased. Collectively, these results indicate that Ring1A/B-mediated Polycomb silencing functions downstream of the core transcriptional regulatory circuitry to maintain ES cell identity.